rac-4,8-Divinylbicyclo[3.3.1]nonane-2,6-dione - Orentas, Edvinas (International Union of Crystallography, 2009)
The title compound, C(13)H(16)O(2), is a chiral bicyclic structure composed of two fused cyclohexane rings possessing both boat and chair conformations. The molecules are packed in enantiopure columns which are pairwise linked forming an overall racemic solid; within the column pairs the packing is governed by weak dipole–dipole interactions stemming from stacked carbonyl functionalities (CO(centroid)–CO(centroid) distance = 3.290 Å).